cGAS-STING-mediated DNA sensing maintains CD8 + T cell stemness and promotes antitumor T cell therapy - Li, Wenwen; Lu, Lu; Lu, Juanjuan; Wang, Xinran; Yang, Chao; Jin, Jingsi; Wu, Lingling; Hong, Xiaochuan; Li, Fanlin; Cao, Dongqing; Yang, Yuanqin; Wu, Meng; et al. (Science translational medicine, 2020)
Although cGAS-STING-mediated DNA sensing in tumor cells or phagocytes is central for launching antitumor immunity, the role of intrinsic cGAS-STING activation in T cells remains unknown. Here, we observed that peripheral blood CD8 T cells from patients with cancer showed remarkably compromised expression of the cGAS-STING cascade. We demonstrated that the cGAS-STING cascade in adoptively transferred CD8 T cells was essential for antitumor immune responses in the context of T cell therapy in mice. Mechanistically, cell-autonomous cGAS and STING promoted the maintenance of stem cell-like CD8 T cells, in part, by regulating the transcription factor TCF1 expression. Moreover, autocrine cGAS-STING-mediated type I interferon signaling augmented stem cell-like CD8 T cell differentiation program mainly by restraining Akt activity. In addition, genomic DNA was selectively enriched in the cytosol of mouse CD8 T cells upon in vitro and in vivo stimulation. STING agonism enhanced the formation of stem-like central memory CD8 T cells from patients with cancer and potentiated antitumor responses of CAR-T cell therapy in a xenograft model. These findings advance our understanding of inherent cGAS-STING activation in T cells and provide insight into the development of improved T cell therapy by harnessing the cGAS-STING pathway for cancer immunotherapy.